The Mediation Role Of Training On The Relationship Between The Competencies Of The Building Information Modelling Manager And The Project Performance - Ibrahim, Farah Salwati (2023)
A competent BIM Manager is important in the construction industry, as their roles and responsibilities are needed throughout the project lifecycle. As a result, the right competencies are critical for a BIM Manager, as they will influence project performance through the way he or she manages it. This study aims to explore the mediating role of training on the relationship between the competencies of the Building Infromation Modelling (BIM) Manager and project performance. In this study, four objectives were constructed, and a concurrent mixed-methods approach was used. The interviews were conducted among the 8 BIM-SMEs, and the results were analysed through content analysis. Meanwhile, for quantitative method, questionnaire were distributed to 58 BIM Managers which the data were analysed using PLS-SEM tool. A triangulation of qualitative and quantitative findings was performed to compare, contrast, and synthesise the data. The findings revealed that only 5 out of 8 competency sets which are administration (AD), functional (FC), managerial (MG), implementation (IM), and research & development (RD) were important at the intermediate to expert levels, while another three competency sets; technical (TC), operational (OP), and supportive (SP) were at the basic to intermediate level. For the project performance constructs, the project diagnosis, reliability, and monitoring were relevant measurements.